Wild relatives and new breeding techniques sustain Fe and Zn biofortified crop farming systems under climate change and emergencies - Xu, C.; Wang, L.; Yin, J.; Qi, L.; Feng, Y.; Ji, Y.; Li, Y.; Chang, S.; Yuan, P.; Zhang, Z.; Shan, Y.; Hoekenga, O.A.; et al. (Informa UK Limited, 2024)
There are about two billion people suffered malnourished because of the failing global food system, historical emphasis on crop yield, notably lacking in Fe and Zn. Breeding biofortified staple crops is a sustainable strategy to tackle this issue, but it poses challenges, primarily due to limited genetic resources in modern breeding populations. Simultaneously, global climate change, marked by rising temperatures and increased atmospheric CO2, threatens the stability of micronutrient concentrations in harvest organs, such as gain, fruit, root, tubers etc. The rich biodiversity of crop wild relatives, including wild species, landraces, and natives, offers a promising genetic response to climate change. Advanced breeding technologies, like marker-assisted selection breeding, genomic selection, gene editing provide opportunities to enhance Fe and Zn concentrations in staple crops, such as rice, maize, wheat, cassava, etc. Genome-wide association studies and population genetics research will help found qualitative genes and major-effect homeostasis genes for Fe and Zn, which purpose is to uncover the molecular mechanisms governing Fe and Zn regulation in staple crops. Despite these strides, enhancing Fe and Zn bioavailability for human, requires considering absorption enhancers and inhibitors, rather than solely increasing concentrations. Absorption testing systems like the Caco-2 cell line, elucidating the meta-process of Fe and Zn absorption in the human body should be considered when breeding Fe and Zn biofortified crops through traditional and molecular breeding.